Multidrug-Resistant ESBL-Producing E. coli in Clinical Samples from the UK - Delveen R. Ibrahim; Christine E. R. Dodd; Dov J. Stekel; Remilekun T. Meshioye; Mathew Diggle; Michelle Lister; Jon L. Hobman (Antibiotics, 2023)
Globally, cephalosporin therapy failure is a serious problem for infection control. One causative agent of cephalosporin-resistant infections is multidrug-resistant (MDR) E. coli producing extended-spectrum β-lactamases (ESBLs) and/or plasmid-encoded AmpC (pAmpC) β-lactamases. We evaluated the occurrence of ESBL/pAmpC genetic determinants in phenotypically MDR E. coli isolated from clinical samples of blood, faeces, ear effusion, urine and sputum from a UK hospital. Phenotypic resistance profiling for 18 antibiotics (from seven classes) showed that 32/35 isolates were MDR, with resistance to 4–16 of the tested antibiotics. Of the isolates, 97.1% showed resistance to ampicillin, 71.4% showed resistance to co-amoxiclav, cefotaxime, ceftazidime and ceftiofur, and 68.5% showed resistance to cefquinome. blaCTX-M, blaTEM and blaOXA-1 genes were detected in 23, 13 and 12 strains, respectively, and Intl1 was detected in 17 isolates. The most common subtypes among the definite sequence types were CTX-M-15 (40%) and TEM-1 (75%). No E. coli isolates carried pAmpC genes. Significant correlations were seen between CTX-M carriage and cefotaxime, ceftiofur, aztreonam, ceftazidime and cefquinome resistance; between blaCTX-M, blaTEM and blaOXA-1 carriage and ciprofloxacin resistance; and between Intl1 carriage and trimethoprim/sulfamethoxazole resistance. Thus, MDR phenotypes may be conferred by a relatively small number of genes. The level and pattern of antibiotic resistance highlight the need for better antibiotic therapy guidelines, including reduced use and improved surveillance.